Activity of Loan Funds and Guarantee Funds in the Aspect of Regional Development in Poland - Przemyslaw PLUSKOTA (Communications of International Proceedings, 2020)
The literature describes numerous research studies regarding the impact of financial institutions on the economy. Most of them pertain to the impact of national financial institutions on the national economy, proving their positive influence on economic development. However, there are studies that have shown a negative correlation. Generally, the correlation depends on the size of the financial sector and the kind of economy. However, there are few research studies and analyses that focus on regional financial institutions and their impact on development of the regions in which they operate. Even fewer address the activity of non-bank financial institutions and their impact on their environment. Global or national financial institutions serve local entrepreneurs without taking into account the specific nature of their businesses or benefits for the region. Therefore, it seems purposeful to have a look at the activity of regional financial institutions which many a time have taken root in the local community and support micro- and small enterprises in the regions. Even though the scale and effects of their operation are much smaller, their positive impact on the business and regional growth cannot be unappreciated. This article describes the functioning of non-bank financial institutions in Poland – loan funds and credit guarantee funds – and their impact on the regional economy. In most regions, a well-developed system of such institutions and their efficient operation in the area of granting loans and credit guarantees translate into improved economic indicators and benefits for enterprises. It is therefore possible to state that the financial institutions have a positive impact on both regional development and the operation of the the micro-, small and medium enterprises sector. Nevertheless, loan funds and credit guarantee funds will have to face some challenges. National authorities will need to recognise their contribution to business support, while regional authorities will have to meet the capital requirements so as to increase the effectiveness of their operation.
Keywords: Loan Funds; Guarantee Funds; Financial Instruments; Regional Development